Penerapan Prinsip Digital Citizenship dalam Kebijakan Publik : Studi Kasus Negara Berkembang - Ahmad Muhammad Mustain Nashoha; Ashfiyah Nur Atqiya; Istna Ramadhan; Silfia Na’imatul’ Ilmi; Shifa Artha Khoirunnisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The implementation of digital citizenship in public policy in developing countries still faces various challenges. Therefore, a comprehensive strategy is needed, including improving digital access, digital literacy education, and supportive regulations for active and responsible citizen engagement. This study provides insights for policymakers in designing more inclusive regulations to strengthen citizen participation in the digital era. In the research on the Application of Digital Citizenship Principles in Public Policy: Case Study of Developing Countries, the methods used refer to the approaches that have been used in the journals in the bibliography.